The Use of a Chelating Ion-Exchange Resin to Evaluate the Effects of the Extracellular Calcium Concentration on Adenosine Diphosphate Induced Aggregation of Human Blood Platelets - Heptinstall, Stanley (Thrombosis and Haemostasis, 1976)
1. An ion-exchange resin, Chelex 100, has been used to prepare suspensions of human blood platelets in calcium and magnesium depleted plasma.2. Extracellular calcium is required for platelet aggregation when induced by adenosine diphosphate (ADP). Magnesium only supports aggregation provided that a small amount of calcium is present in the plasma.3. The extent of platelet aggregation depends upon the concentration of calcium in the plasma. There is an optimum concentration of calcium with which the maximum amount of aggregation is obtained in response to any single concentration of ADP. This optimum calcium concentration is below the physiological level. Higher calcium concentrations reduce the extent of aggregation by enhancing the rate of disaggregation and high magnesium concentrations have the same effect. It is possible that free ADP levels are reduced as a result of ADP-divalent cation complex formation.4. Platelets were found to contain 18.6 (S.D. ±1.1) × 10–6 mol Ca and 9.3 (S.D. ±1.0) × 10–6 mol Mg per 1011 cells.